Vitamin D categories and postpartum thyroid function in women with hypothyroidism - Chen, Yanrong; Zhang, Sijing; Hu, Lingling; Dong, Lun; Liu, Qiuhong; Liu, Yunting; Cheng, Wei; Liu, Dongfang; Yang, Gangyi; Li, Ke (Frontiers in Nutrition, 2022)
Objective: To analyze the related factors for the evolution of postpartum thyroid function in women with hypothyroidism and explore the effects of vitamin D categories. Methods: Thyroid hormones, thyroid autoantibody and serum 25OHD levels were continuously recorded from the first trimester of pregnancy (T1) to the 12th postpartum month. Logistic regression analysis and Cox regression analysis were used to screen the related factors of postpartum thyroid function, and Latent Class Growth Model was performed to analyze the trajectory characteristics of serum 25OHD levels. Results: Total 252 pregnant women with hypothyroidism were enrolled in the study. In the 12th month postpartum, 36.5% of the patients had improved thyroid function, 37.3% had continued hypothyroidism and 26.2% had developed thyroid dysfunction. Vitamin D sufficiency, positive TPOAb and positive TgAb in T1 were independent prognostic factors for the evolution of postpartum thyroid function. Vitamin D sufficiency in T1 was illustrated as an independent factor for improved postpartum thyroid function, but the protective effect for developed postpartum thyroid dysfunction was only confirmed in TPOAb-positive patients. Cox regression analysis further confirmed the effects of vitamin D categories. Notably, the high-level 25OHD trajectory during pregnancy and postpartum could predict improved postpartum thyroid function and decrease the risk of developed postpartum thyroid dysfunction. Conclusions: Appropriate vitamin D nutrition during pregnancy and postpartum may be beneficial to the evolution of postpartum thyroid function in women with hypothyroidism.